BETWEEN FREEDOM AND SLAVERY: EPISTEMOLOGICAL ASSUPTIONS FOR LABOR LAW (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
It analyzes the concept of Labor Law and its contrast in relation to the concept of slavery, both at the national level and in the general scope of the concept. To better understand this phenomenon, it was identified the needing to outline three major theories about human freedom, which deal with this topic in its political, ethical and pedagogical aspects. Therefore, a hypothetical-deductive methodology was adopted to expose the theories of freedom, associating them with their importance in the sphere of autonomy and human dignity.